Application of Geospatial Analysis and Augmented Reality Visualization in Indoor Advertising - Jamali, Bahman; Sadeghi-Niaraki, Abolghasem; Arasteh, Reza (International Journal of Geography and Geology, 2014)
In recent years, capabilities of modern smartphones offer the potential to design tools that support new form of marketing, advertising and providing smarter business systems. The features and ubiquity of mobile technologies provide opportunities for developing new experiences that support a pervasive advertising. The use of ubiquitous computing technologies for advertising purposes presents huge opportunities and challenges for our future and bring new concept as an Ubi-Advertising. Indoor Advertising reaches consumers from an uncluttered, captive, eye-level vantage point, making it unavoidable. In this contribution, a concept to estimate installation’s location of indoor advertising billboards and signs in 3D visualization space has been introduced. This study proposes a new framework to apply capabilities of Ubiquitous Geographic Information Systems (UbiGIS) and spatio–temporal modeling to determine the best location for installing advertising billboards and signs in indoor environments. For this purpose, first, it used 3D visibility analysis for modelling 3D environment. After identifying suitable location, the result was used to create a location-based service (LBS). Then, application software was developed based on Augmented Reality (AR) technology for visualizing advertisements in the effective way. AR provides additional information about the ads and creates interactive content. Milad-e-Noor shopping center in Tehran city was selected and the model was implemented in this area. The results prove the merit of this research.